MYSIR’s Abstracts 4: Annual Scientific Meeting 2022 - Interventional Radiology, Malaysian Society of (The Interventionalist Journal, 2022)
MYSIR’s Abstracts 4 1. EP13: PULMONARY ARTERY ANEURYSM – TO GLUE OR TO COIL? 2. EP14: ENDOVASCULAR MANAGEMENT OF A MURAL TYPE OF VEIN OF GALEN MALFORMATION IN A 5 YEAR OLD, FILIPINO CHILD WITH DEVELOPMENTAL DELAY AND SEIZURES: A CASE REPORT 3. EP15: PERCUTANEOUS COIL EMBOLISATION OF HEPATIC ARTERY MYCOTIC ANEURYSM 4. EP16: HEPATIC FALCIFORM ARTERY AS AN ANATOMICAL VARIANT AND ITS CLINICAL SIGNIFICANCE IN CHEMOEMBOLISATION 5. EP17: PERCUTANEOUS TRANSHEPATICCHOLECYSTIC PLACEMENT OF UNCOVERED STENT IN THE COMMON BILE DUCT AND PERCUTANEOUS CHOLECYSTOMY TUBE INSERTION 6. EP18: CRYOABLATION AS AN EFFECTIVE TREATMENT FOR LUNG METASTASES SECONDARY TO UNDIFFERENTIATED SOFT TISSUE SARCOMA 7. EP19: SUPER-SELECTIVE TRANSARTERIAL GLUE EMBOLIZATION (TAGE) OF ACQUIRED UTERINE ARTERIOVENOUS MALFORMATIONS (AVMS) - A CASE REPORT